Wind effects on the long‐distance migration of GPS‐tracked adult ospreys Pandion haliaetus from Germany - Bernd‐Ulrich Meyburg; Daniel Holte (Journal of Avian Biology, 2023)
Birds that repeatedly visit distinct places along their migratory routes in consecutive years must be able to navigate to these places and respond appropriately to unfavourable wind conditions. This study analysed the migratory routes, repeatedly‐visited areas and responses to sidewinds of 15 GPS‐tracked adult ospreys Pandion haliaetus from northeast Germany migrating to their wintering sites in Africa and back. We determined stopovers and intermediate goal areas and performed repeatability estimations on timing and migratory paths in four regions. The orientation behaviour of the ospreys was analysed with regard to perpendicular wind components at each GPS point during autumn and spring migrations. Generalised linear mixed models were used to test the dependence of orientation behaviour on region and the distance to the next goal. The findings showed that ospreys demonstrate high fidelity to migratory paths in autumn and spring, as well as to the timing of migration in autumn; and sidewinds are predominantly compensated, especially when sidewinds are strong. Furthermore, during autumn migration, the proportion of compensation increases in most regions with decreasing distances to the next goal; however, during spring migration, drift behaviour was detected more often at smaller distances to the next goal than at higher distances in the regions Mediterranean and central Europe. In general, ospreys compensate for unfavourable sidewinds and utilise supporting tailwinds on their journeys to the wintering sites in Africa and back to central Europe.